2019
DOI: 10.3390/app9153105
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Evaluating the Performance of the Bearing Manufacturing Process

Abstract: Reliability and product process quality are essential in meeting market demand and enhancing competitiveness in the machine tool industry. In addition, manufacturing time performance is also one of the important indices. Therefore, this paper focuses on process quality and manufacturing time and defines a manufacturing time performance index to feedback the acceptance rate of the manufacturing time. The process performance evaluation chart delineated the observations of variations in various workstations, and,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 25 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…A lot of studies have indicated that if the required process capability of a product is v , then the required value v of the process capability of an individual quality characteristic must be greater than v [2,30,31]. As mentioned above, when the process capability for each quality characteristic meets the requirement, it can be claimed as a qualified product or component.…”
Section: Estimations Of Process Quality Indicesmentioning
confidence: 99%
“…A lot of studies have indicated that if the required process capability of a product is v , then the required value v of the process capability of an individual quality characteristic must be greater than v [2,30,31]. As mentioned above, when the process capability for each quality characteristic meets the requirement, it can be claimed as a qualified product or component.…”
Section: Estimations Of Process Quality Indicesmentioning
confidence: 99%
“…In the other aspect, there are also techniques improving function reconfiguration, control systems with networks [136], stiffness, and high precision. The manufacturing process of key components also has a significant role in sustainable machine tool design and manufacturing, like the bearing manufacturing process [137]. The optimization of moving component like the guideway and spindle system could decrease energy consumption by reducing mass with new structure or material [138].…”
Section: Other Technologiesmentioning
confidence: 99%
“…Duan et al [24] put forward a reliability modeling and evaluating methodology for a repairable, non-series, multistate FMS with finite buffers by using an improved vector universal generation function to satisfy the market demands on capacity and capability of the system. Chen et al [25] proposed a process performance evaluation chart to examine the manufacturing performance of bearing connectors, which can also be used for multiple evaluations of manufacturing performance in other manufacturing industries. Kim and Hwangbo [26] investigated the innovation process for smart manufacturing in the domain of synthetic rubber and its vulcanization process, as well as a real-time sensing technology to the realization of a smart manufacturing environment by building cloud-based infrastructure and models for the pre-detection of defects.…”
Section: Introductionmentioning
confidence: 99%